Sound Activated Sorting Bin - Muhamad Akmal Hakimi Azhar; Nur Syazwani Nabila Mohd Sulaiman; Nur Saidatul Zalikha Mohamad Isa; Nor Baizura Hamid; Siti Nooraiin Mohd Razali (Multidisciplinary Applied Research and Innovation, 2026)
Excessive waste generation and inefficient recycling processes are among the serious environmental concerns. The study developed a Sound Activated Sorting Bin (SASB) to automate waste sorting using sound recognition technology. The process aims to improve recycling rates by effectively sorting paper, plastic, and metal waste without human intervention. The proof of concept uses an ESP32 microcontroller to process sound using a microphone, an E18 IR sensor to identify objects, and servo motors for mechanical sorting. It is powered by an 11.1V LiPo battery, features a three compartment modular setup, and includes real-time audio feedback. The system was tested with 300 sorting attempts under laboratory conditions. Results indicated 75% overall classification accuracy which means only 25% error rate, with error rates decreasing from 29% to 21% across trials. The system also achieved a consistent processing time of 0.41 seconds in later trials, and a mean of 2.27 seconds per item overall. This research introduces an innovative waste management system that reduces manual sorting requirements, demonstrates the viability of sound-based separation, and provides a scalable solution for diverse environments. As the SASB is compact and energy-efficient, it is suitable for installation in homes, offices, and public spaces, with much potential to streamline recycling habits and augment sustainability efforts.